2015
DOI: 10.1186/s12936-015-0946-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide as adjunctive therapy for severe malaria: a randomized controlled trial

Abstract: BackgroundSevere malaria remains a major cause of childhood mortality globally. Decreased endothelial nitric oxide is associated with severe and fatal malaria. The hypothesis was that adjunctive inhaled nitric oxide (iNO) would improve outcomes in African children with severe malaria.MethodsA randomized, blinded, placebo-controlled trial of iNO at 80 ppm by non-rebreather mask versus room air placebo as adjunctive treatment to artesunate in children with severe malaria was conducted. The primary outcome was th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
68
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 29 publications
0
68
1
Order By: Relevance
“…A clinical trial in pediatric malaria showed that inhaled nitric oxide did not affect biomarkers of severe disease. 91 More recently, the role of NO in severe malaria has also implicated the angiogenic factor Ang-2 which is stored in Weibel-Palade bodies (WPB) in endothelial cells and secreted in conjunction with von Willebrand Factor. 92 The decreased vascular NO bioavailability found in severe malaria is proposed to increase exocytosis of WPB with a resultant increase in Ang-2 release.…”
Section: Host Inflammatory Mediatorsmentioning
confidence: 99%
“…A clinical trial in pediatric malaria showed that inhaled nitric oxide did not affect biomarkers of severe disease. 91 More recently, the role of NO in severe malaria has also implicated the angiogenic factor Ang-2 which is stored in Weibel-Palade bodies (WPB) in endothelial cells and secreted in conjunction with von Willebrand Factor. 92 The decreased vascular NO bioavailability found in severe malaria is proposed to increase exocytosis of WPB with a resultant increase in Ang-2 release.…”
Section: Host Inflammatory Mediatorsmentioning
confidence: 99%
“…The study was conducted according to Declaration of Helsinki and International Council for Harmonisation guidelines on Good Clinical Practice. Serum samples were collected from children presenting to the Jinja Regional Pediatric Referral Hospital who met World Health Organization criteria for CM (26). Sera were collected at admission and stored at -80°C until use.…”
Section: Patient Samplesmentioning
confidence: 99%
“…The first study compared 88 children who received iNO at 80 ppm with 92 children who received placebo (all subjects received artesunate i.v.) and showed that iNO failed to reduce angiopoietin-2 (Ang-2; a marker of endothelial dysfunction) levels and had no effect on mortality (18). Methemoglobinemia did develop in 25% of children in the treated group, but without sequelae.…”
Section: Nitric Oxidementioning
confidence: 99%
“…Nevertheless, the use of gaseous therapy for malaria is incipient. At the moment, only two phase II clinical trials have been completed, both examining the effect of NO administration for children with severe malaria (18,19). Nevertheless, some in vitro and in vivo studies-using the experimental cerebral malaria (ECM) murine model-have shed light on the topic and opened perspectives for adjunctive therapies in malaria.…”
mentioning
confidence: 99%
See 1 more Smart Citation